Association between vascular endothelial - Hiroyuki Kumamoto (J Oral Pathol Med)
Expression of vascular endothelial growth factor (VEGF), a major angiogenic factor, and microvessel density (MVD), assessed by the use of anti-CD34 antibody, were immunohistochemically examined in benign and malignant ameloblastomas, as well as tooth germs, to clarify the possible role of angiogenesis in epithelial odontogenic tumors.